Analysis of Gear Bulk Temperature Field and Transmission Errors Based on Workbench - Guo Heng; Liu Zhuoting; Sun Yujiu; Tang Jie (Jixie chuandong)
The finite element analysis models of the gear temperature field and transmission error are established based on Workbench. The gear temperature field at different revolutions and torques, the gear transmission errors at different speeds and temperatures are analyzed. Simulation of gear temperature field through Ansys Workbench, the distribution results of gear temperature field and gear meshing line temperature field are obtained; the temperature result is used as a load in the simulation study of gear transmission error by means of indirect coupling, and the simulation result of gear transmission error is obtained. The results show that with the increase of gear speed and torque, the gear temperature presents an overall upward trend; the linear relationship between gear revolution, gear torque and temperature variation of gear meshing line is approximately presented. In the simulation analysis of gear transmission error, with the increase of the gear speed and temperature, gear transmission error curve moves up and down respectively, but the peak-to-valley value of the gear transmission error curve does not change much; the gear speed and temperature are approximately linearly related to the variation of the gear transmission errors.